The potential Effects of the “melting” of state borders on the border areas of Hungary - Pénzes, János; Tagai, Gergely (Észak-magyarországi Stratégiai Füzetek, 2012)
The effect of borders can have important impact on the possibilities of spatial development. Many theoretical, methodological and empirical questions can arise about the investigation of this phenomenon and about the interpretation of it. In this domain of interests the issues of integration processes and their relation to borders (and border effects) have significant role. In this study, focusing primarily on border areas, many important and popular methods of analysing the effect of economic integration are presented. One of the most spectacular methods – the potential model – is investigated in detail in order to analyse the theoretical cross-border effect of the most important economic centres on the border areas of Hungary